if f:R+->R+ is a polynominal function satisfying the equation f(f(x))=6x-f(x), then f(17)=?
Answers
Answered by
2
Step-by-step explanation:
Given if f:R+->R+ is a polynomial function satisfying the equation f(f(x))=6x - f(x), then f(17)=?
- Now f (f(x) = 6x – f(x)
- So f (f(x) is something of f(x)
- The only possibility is f(x) is a linear function.
- So f(x) = ax + b
- Therefore f(ax + b) = 6x – (ax + b)
- So f(ax + b) = (6 – a)x – b
- [ Now in place of x we can put ax + b
- So f(ax + b) = a(ax + b) + b]
- So a (ax + b) + b = (6 – a)x – b
- So a^2 x + ab + b = (6 – a) x – b
- So a^2 = 6 – a
- So a^2 + a – 6 = 0
- So a^2 + 3a – 2a – 6 = 0
- Or a(a + 3) – 2(a + 3) = 0
- Or (a + 3) (a – 2) = 0
- Or a = - 3, 2
- Now for the constant term we have
- So ab + b = - b
- Or ab + 2b = 0
- Or b(a + 2) = 0
- Or b = 0
- Now f(x) = ax + b if b = 0,
- So f(x) = ax
- So possibilities will be
- So f(x) = 2x if a = 2
- So f(17) = 2(17) = 34
- So f(x) = - 3x if a = - 3
- So f(17) - - 3(17) = - 51
Reference link will be
https://brainly.in/question/7780979
Similar questions